Childhood psoriasis: Disease spectrum, comorbidities, and challenges - Soumajyoti Sarkar; Sandipan Dhar; Siba P Raychaudhuri (Wolters Kluwer Medknow Publications, 2019)
Psoriasis is a chronic, inflammatory, papulosquamous disorder with a variable clinical spectrum. Although it affects population of all age groups, the significance and negative impact of childhood psoriasis is often neglected worldwide. In nearly one-third of the psoriatic population, psoriasis appears during the childhood. In this article, we have focused on different issues and challenges faced during the management of childhood psoriasis. In addition to the varied clinical spectrum and associated comorbidities, in this article, we have given emphasis on the following real needs for childhood psoriasis: (i) psychological and social effects on the affected children, (ii) impact on their family members, and (iii) early diagnosis and management of psoriasis on children with psoriasis. We have concluded the article with the "concept of total care," which is a third dimension for the management of psoriasis.